First Experiences with Incisional Negative Pressure Wound Therapy in a High-Risk Poststernotomy Patient Population treated with Pectoralis Major Muscle Flap for Deep Sternal Wound Infection - Nickl, Stefanie; Steindl, Johannes; Langthaler, Daniel; Nierlich-Hold, Alina; Pona, Igor; Hitzl, Wolfgang; Kocher, Alfred; Happak, Wolfgang; Radtke, Christine; Tzou, Chieh-Han (Journal of Reconstructive Microsurgery, 2018)
Background Radical debridement and wound closure with vascularized flaps has become a standard procedure in the treatment of deep sternal wound infections. Negative pressure incision management systems have been proven to diminish wound infections after sternotomy. In this study, the utility of Prevena Incision Management System (KCI Licensing Inc.) was evaluated in obese patients who received unilateral pectoralis major flap for the treatment of deep sternal wound infections.Methods The outcome and wound-related complication rates of 19 obese patients (mean body mass index, 33.7) treated for deep sternal wound infection with pectoralis major muscle flap in combination with Prevena between 2011 and 2016 were compared with 28 obese patients treated with conventional wound dressing only between 2000 and 2010.Results In patients additionally treated with Prevena, significantly fewer surgical revisions due to wound-related complications were necessary as compared with patients who received conventional wound dressing (5.3 vs. 32.1%, p = 0.034). A significantly shorter ICU length of stay (median 0 vs. 3.5 days, p < 0.001) and a trend toward shorter length of hospitalization (median 14 vs. 19.5 days after pectoralis major flap) could be observed.Conclusion The application of Prevena significantly reduced revision surgery rates in obese patients treated with unilateral pectoralis major flap for deep sternal wound infections.
Keywords: deep sternal wound infection; pectoralis major muscle flap; surgical incision management system